Modulation of T-cell function by myeloid-derived suppressor cells in hematological malignancies - Bhardwaj, Vaishali; Ansell, Stephen M. (Frontiers in Cell and Developmental Biology, 2023)
Myeloid-derived suppressor cells (MDSCs) are pathologically activated neutrophils and monocytes that negatively regulate the immune response to cancer and chronic infections. Abnormal myelopoiesis and pathological activation of myeloid cells generate this heterogeneous population of MDSCs. They are characterized by their distinct transcription, phenotypic, biochemical, and functional features. In the tumor microenvironment (TME), MDSCs represent an important class of immunosuppressive cells that correlate with tumor burden, stage, and a poor prognosis. MDSCs exert a strong immunosuppressive effect on T-cells (and a broad range of other immune cells), by blocking lymphocyte homing, increasing production of reactive oxygen and nitrogen species, promoting secretion of various cytokines, chemokines, and immune regulatory molecules, stimulation of other immunosuppressive cells, depletion of various metabolites, and upregulation of immune checkpoint molecules. Additionally, the heterogeneity of MDSCs in cancer makes their identification challenging. Overall, they serve as a major obstacle for many cancer immunotherapies and targeting them could be a favorable strategy to improve the effectiveness of immunotherapeutic interventions. However, in hematological malignancies, particularly B-cell malignancies, the clinical outcomes of targeting these MDSCs is a field that is still to be explored. This review summarizes the complex biology of MDSCs with an emphasis on the immunosuppressive pathways used by MDSCs to modulate T-cell function in B-cell malignancies including non-Hodgkin lymphoma and chronic lymphocytic leukemia. In addition, we describe the challenges, therapeutic strategies, and clinical relevance of targeting MDSCs in these diseases.